2010
DOI: 10.1029/2009wr008903
|View full text |Cite
|
Sign up to set email alerts
|

Mixing effects on apparent reaction rates and isotope fractionation during denitrification in a heterogeneous aquifer

Abstract: [1] Gradients in contaminant concentrations and isotopic compositions commonly are used to derive reaction parameters for natural attenuation in aquifers. Differences between field-scale (apparent) estimated reaction rates and isotopic fractionations and local-scale (intrinsic) effects are poorly understood for complex natural systems. For a heterogeneous alluvial fan aquifer, numerical models and field observations were used to study the effects of physical heterogeneity on reaction parameter estimates. Field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 89 publications
3
131
0
Order By: Relevance
“…Fractionation coefficients ( 15 ε) derived from both the cross-spring analysis and (5.27-7.49) the Ichetucknee River springs time series (7.37) are within the lower range of values reported for other aquifers (Mariotti, 1986;Bohlke et al, 2002;Green et al, 2008), and other marine and freshwater environments (Sigman et al, 2005;Granger et al, 2008), but are lower than some recent experimental values (Knoller et al, 2011). These relatively low values may indicate diffusion-constrained NO in the UFA (Sebilo et al, 2003), but could also be an artefact of mixing between distinct water sources (Green et al, 2010).…”
Section: Evidence For Denitrification In the Upper Floridan Aquifermentioning
confidence: 76%
See 2 more Smart Citations
“…Fractionation coefficients ( 15 ε) derived from both the cross-spring analysis and (5.27-7.49) the Ichetucknee River springs time series (7.37) are within the lower range of values reported for other aquifers (Mariotti, 1986;Bohlke et al, 2002;Green et al, 2008), and other marine and freshwater environments (Sigman et al, 2005;Granger et al, 2008), but are lower than some recent experimental values (Knoller et al, 2011). These relatively low values may indicate diffusion-constrained NO in the UFA (Sebilo et al, 2003), but could also be an artefact of mixing between distinct water sources (Green et al, 2010).…”
Section: Evidence For Denitrification In the Upper Floridan Aquifermentioning
confidence: 76%
“…For the subset of springs for which 3 H/ 3 He ages were available, we estimated zero-order denitrification rates as the concentration of excess N 2 divided by water age (Green et al, 2008). Because we lack data for discrete geochemical end-members within each spring, we are unable to quantitatively address the effects of mixing (Green et al, 2010) on our estimates of denitrification rates or O 2 thresholds.…”
Section: Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, assumptions concerning reaction kinetics can be validated by comparing model results to measured concentration and CSIA data (D'Affonseca et al, 2011;Pooley et al, 2009;Prommer et al, 2009;Atteia et al, 2008). IF-RTMs have also proven useful to study the transformation of the agrochemical pollutant nitrate (Chen and MacQuarrie, 2004;Green et al, 2010). As opposed to the simulation of concentrations of a degrading contaminant, which solely yields a certain concentration reduction between the emission source and a downgradient point, these studies have demonstrated that IFRTMs allow for the quantification of in situ degradation and the distinction between destructive and non-destructive processes.…”
Section: S R Lutz Et Al: Potential Use Of Csia In River Monitoringmentioning
confidence: 99%
“…earthen manure storage, temporary manure piles, or fertilizer) and the 10 complexity of hydrogeologic systems (Spalding and Exner, 1993;Rodvang et al, 2004;Showers et al, 2008;Kohn et al, 2016). These spatial and temporal variations can result in complex subsurface solute distributions that are difficult to interpret using classical transect studies or numerical groundwater models (Green et al, 2010;Baily et al, 2011).…”
Section: Identification Of the Sources And Fate Of No3mentioning
confidence: 99%